2004
DOI: 10.1097/00000542-200403000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tyrosine Kinase in Desflurane-induced Preconditioning

Abstract: Desflurane-induced preconditioning does not depend on tyrosine kinase activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…6 In contrast, activation of tyrosine kinase is required in IPC 29,30 but not necessarily in pharmacological preconditioning. 31 During the early phase of reperfusion, it is now well established that IPC activates the RISK pathway. 32,33 In addition, many pharmacological agents, such as adenosine agonists, bradykinin, atorvastatin, urocortin, insulin, and cardiotrophin-1, all protect the heart by activating the RISK pathway when given at the beginning of reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…6 In contrast, activation of tyrosine kinase is required in IPC 29,30 but not necessarily in pharmacological preconditioning. 31 During the early phase of reperfusion, it is now well established that IPC activates the RISK pathway. 32,33 In addition, many pharmacological agents, such as adenosine agonists, bradykinin, atorvastatin, urocortin, insulin, and cardiotrophin-1, all protect the heart by activating the RISK pathway when given at the beginning of reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…There is also strong recent evidence demonstrating that desflurane confers a preconditioning‐like cardioprotection ( Toma et al , 2004 ; Tsai et al , 2004 ; Smul et al , 2006 ). This protection appears to involve both sarcolemmal and mitochondrial K ATP channels ( Toller et al , 2000 ) and mediated by NO ( Smul et al , 2006 ), but does not involve tyrosine kinase activation ( Ebel et al , 2004 ). Recently it has been suggested that signal transduction pathways associated with β1‐adrenergic receptor mediate anaesthetic preconditioning for desflurane and sevoflurane ( Lange et al , 2006 ).…”
Section: Anaesthetics As Cardioprotective Agentsmentioning
confidence: 99%
“…Modern volatile anaesthetics as elicitors of cardiac preconditioning have been effectively demonstrated in cell culture experiments [1,2] and animal models [3,4,5,6]. There is also supporting evidence from clinical studies that anaesthetic-induced preconditioning (APC) is protective in the clinical setting [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent molecular investigations of DES-PC were conducted with focus on specific targets known from IPC [2,3,4,5,11,12] but the overall picture of the underlying mechanisms is still lacking. A couple of studies even showed that the signalling pathways may differ from IPC [6,13]. …”
Section: Introductionmentioning
confidence: 99%